Amantadine extended release for levodopa‐induced dyskinesia in Parkinson's disease (EASED Study). Issue 6 (4th February 2015) - Pahwa, Rajesh; Tanner, Caroline M.; Hauser, Robert A.; Sethi, Kapil; Isaacson, Stuart; Truong, Daniel; Struck, Lynn; Ruby, April E.; McClure, Natalie L.; Went, Gregory T.; Stempien, Mary Jean
Abstract ADS‐5102 is a long‐acting, extended‐release capsule formulation of amantadine HCl administered once daily at bedtime. This study investigated the safety, efficacy, and tolerability of ADS‐5102 in Parkinson's disease (PD) patients with levodopa‐induced dyskinesia. This was a randomized, double‐blind, placebo‐controlled, parallel‐group study of 83 PD patients with troublesome dyskinesia assigned to placebo or one of three doses of ADS‐5102 (260 mg, 340 mg, 420 mg) administered daily at bedtime for 8 weeks. The primary efficacy analysis compared change from baseline to week 8 in Unified Dyskinesia Rating Scale (UDysRS) total score for 340 mg ADS‐5102 versus placebo. Secondary outcome measures included change in UDysRS for 260 mg, 420 mg, Fatigue Severity Scale (FSS), Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS‐UPDRS), patient diary, Clinician's Global Impression of Change, and Parkinson's Disease Questionnaire (PDQ‐39). ADS‐5102 340 mg significantly reduced dyskinesia versus placebo (27% reduction in UDysRS, P = 0.005). In addition, ADS‐5102 significantly increased ON time without troublesome dyskinesia, as assessed by PD patient diaries, at 260 mg (P = 0.004), 340 mg (P = 0.008) and 420 mg (P = 0.018). Adverse events (AEs) were reported for 82%, 80%, 95%, and 90% of patients in the placebo, 260‐mg, 340‐mg, and 420‐mg groups, respectively. Constipation, hallucinations, dizziness, and dry mouth were the most frequent AEs. Study withdrawal rates were 9%, 15%, 14%, and 40% for the placebo, 260‐mg, 340‐mg, and 420‐mg groups, respectively. All study withdrawals in the active treatment groups were attributable to AEs. ADS‐5102 was generally well tolerated and resulted in significant and dose‐dependent improvements in dyskinesia in PD patients. © 2015 Adamas Pharmaceuticals, Inc. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.